Dietary mannan oligosaccharide improves growth performance, muscle oxidative status, and meat quality in broilers under cyclic heat stress. (July 2018) - Cheng, Yefei; Du, Mingfang; Xu, Qiao; Chen, Yueping; Wen, Chao; Zhou, Yanmin
Abstract: This study investigated the effects of dietary mannan oligosaccharide (MOS) supplementation on growth performance, serum corticosterone level, and antioxidant ability, meat quality as well as chemical composition of breast muscle in broilers exposed to cyclic heat stress (HS). 144 one-day-old male broiler chicks (Arbor Acres plus) were randomly allocated to 3 treatments with 6 replicates each. Broilers in the control and HS groups were fed a basal diet, and in the MOS group were given the basal diet supplemented with 1 g/kg MOS for 42 days, respectively. The temperature was maintained 32–33 °C for the first 3 days for all broilers, and it was gradually reduced by 3 °C per week to a final temperature of 20 °C in the control group, whereas it remained unchanged for 8 h and reduced to the same level to the control group for the remaining 16 h daily in the both HS and MOS groups. Compared with the control group, cyclic HS resulted in retarded growth performance and increased serum corticosterone level ( P  < 0.05). The supplementation of MOS promoted growth performance and reduced serum corticosterone concentration in broilers subjected to cyclic HS ( P  < 0.05). Cyclic HS increased drip loss48 h, cooking loss, malondialdehyde accumulation, and moisture content, whereas decreased pH24 h value, glutathione peroxidase (GSH-Px) activity, and crude protein content in the breast muscle ( P  < 0.05). In contrast, dietary MOS supplementation reduced drip loss48 h and malondialdehyde concentration, and increased GSH-Px activity in breast muscle compared with the HS group ( P  < 0.05). The results indicated that dietary MOS supplementation could improve growth performance, and oxidative status and meat quality of breast muscle in broilers under cyclic HS. Highlights: Mannan oligosaccharide promoted growth performance in broilers under heat stress. Mannan oligosaccharide reduced corticosterone level in broilers under heat stress. Mannan oligosaccharide improved muscle oxidative status in heat-stressed broilers. Mannan oligosaccharide enhanced meat quality in broilers exposed to heat stress.